Women's football: sexed bodies and interfering discourse : if gender is the social organisation of sexual difference through various social practices, discourses, and politics of representation, to what extent can the media popularisation of female soccer in South Africa be read as an interference in the hegemonic organisation of gender relations and heteronormativity? - Joseph, Kate (My University, 2012)
Primarily a theoretical piece contributing to debates on heteronormativity and its cognate conceptual fields, the thesis utilises a linguistic version of discourse analysis to investigate a study of representation. The thesis addresses representation of women’s soccer as a site of potential disruption of dominant cultural understandings of gender and sexuality, but also attempts to ‘queer’ dominant categories for making sense of the body in general.
M.A. University of the Witwatersrand, Faculty of Humanities (Political Studies), 2012